EFFECTIVENESS OF INVESTIGATIONS AGAINST PEOPLE OF THE CRIME OF MONEY LAUNDERING BY THE DIRECTORATE OF SPESIAL CRIMINAL RESEARCH OF THE SOUTH SULAWESI REGIONAL POLICE - Amal, A Wahyudi; Hafidz , Ma'ruf; Busthami, Dachran S (IBLAM LAW REVIEW, 2024)
This research was conducted with the aim of (1) Knowing and analyzing the effectiveness of investigations into perpetrators of money laundering crimes by the special criminal investigation directorate of the South Sulawesi Regional Police, (2) Knowing and analyzing the factors that become obstacles, and efforts to overcome obstacles in investigations against perpetrators of money laundering crimes by the special criminal investigation directorate of the South Sulawesi Regional Police. This research method uses primary data and secondary data. Primary data was obtained through interviews, while secondary data was obtained through documents, scientific journals and scientific articles. The results of this research show that: (1) The effectiveness of investigations into perpetrators of money laundering crimes by the South Sulawesi Regional Police Special Directorate is said to be less effective because money laundering cases in 2022 experienced a three-fold increase in the number of cases from 2020 & 2021, even within a period of three years. Lastly, there are cases that are not processed because there are factors that become obstacles in the investigation of criminal acts of money laundering (2) Factors that become obstacles and efforts to overcome obstacles in the investigation of perpetrators of criminal acts of money laundering by the South Sulawesi Dirskremsus, where the factors Obstacles to investigations are: lack of human resources for police investigators handling money laundering cases, differences in law enforcement interpretations, high levels of bank secrecy, lack of compliance by financial service providers, technological capabilities misused by suspects to carry out their modus operandi in such a way as to disguise or even eliminate no trace at all in the transaction. Therefore, based on the research results, it was found that efforts to overcome obstacles in investigating perpetrators of money laundering crimes include: increasing human resources for police investigators, increasing understanding between law enforcers, increasing police access to banking, providing strict sanctions for banks that do not comply)